Optimal thickness of the catalytic nickel coating for the CVD synthesis of carbon nanomaterials - H M Abuhimd; M V Kiyashko; P S Grinchuk (Materials Research Express, 2020)
The effect of the thickness of a catalytic nickel coating deposited on a copper substrate by an electrochemical method on the intensity of formation of carbon nanomaterials in the CVD process was investigated. It was found that the dependence of the specific nanostructured carbon yield on the coating thickness is extremal, with a maximum near 1.5 μ m. Qualitative interpretation of the obtained data is proposed on the basis of the carbon growth mechanisms on the catalytic coating.